The practical skeptic : - McIntyre, Lisa J. (McGraw-Hill Higher Education, 2006)
Using a conceptual organizing framework, The Practical Skeptic: Core Concepts in Sociology is a concise introduction to sociology that focuses on core concepts as the central building blocks for understanding sociology. Written in a lively, very conversational style -- witness such chapter titles as "Science and Fuzzy Objects: Specialization in Sociology" and "Who’s Afraid of Sociology?" --, McIntyre uses numerous pedagogical features to help students grasp key sociological concepts and to learn the essential lesson that there is much that goes on in the social world that escapes the sociologically untrained eye.